Nesfatin-1 may Interfere with Kisspeptin/kiss1 Systemin Gonadal Activity of Female Rats - Sahin, Zafer; Cuce, Gkhan; Ozcan, Mete; Canpolat, Sinan; Gormus, Zulfikare Isik Solak; Kutlu, Selim; Kelestimur, Haluk (Wiley, 2016)
[Abstract Not Available]